The Effect of Workload and Organizational Commitment on Employee Turnover Intention at PT Aeon Riset Teknologi - Stevania S; Shinta Oktafien (STKIP Yapis Dompu, 2023)
Research to see how the workload affects and which is the organizational commitment of PT Aeon Riset Teknologi. This type of research is quantitative using multiple regression analysis techniques. The population in the study was 40 office employees of PT Aeon Riset Teknologi. The sample from the study, which was 40 people, took saturated sampling or became a census, processed using SPSS Windows Version 25. The results of the study show that workload and organizational commitment have a positive effect on PT Aeon Riset Teknologi. The partial coefficient of determination between Workload and Turnover Intention is 0.435, then 43.5% in influencing Turnover Intention. Meanwhile, the partial determination between the Organization's Commitment to Turnover Intention, which is 0.0529, is 5.29% in influencing Turnover Intention. The magnitude of the influence of workload, and commitment with a percentage of 40.8% with the remaining 59.2% influenced by other variables from the research study.